Atorvastatin blocks Sonic Hedgehog medulloblastoma progression through apoptosis - R.E. Gordon; Z.I. Abramova (Учёные записки Казанского университета: Серия Естественные науки, 2017)
Aberrant activation of Sonic Hedgehog signaling transduction leads to formation of numerous malignancies, including medulloblastoma (MB) – the most common malignant pediatric tumor. Earlier, we have shown that endogenous cholesterol acts as a direct activator of the Sonic Hedgehog signaling and is a promising target for treating MB. Histochemical analysis of the effect of atorvastatin, which is widely used in clinical practice as a cholesterol biosynthesis inhibitor, revealed a high level of cell death in the tumor tissue via apoptosis. These data show the potential of using statins for the targeted therapy of medulloblastoma, as well as other Sonic Hedgehog-driven malignancies.